Preparation method of hydrocracking catalyst for increasing ethylene cracking raw material yield

By preparing the catalyst by first preparing the active metal oxide and combining specific components, the problem of active metal covering the acid center during the existing catalyst preparation process is solved, the performance and process efficiency of the catalyst is significantly improved, and high-quality ethylene cracking raw materials are achieved.

CN119819354APending Publication Date: 2025-04-15SINOCHEM QUANZHOU PETROCHEM CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510105989.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

During the preparation process of existing hydrocracking catalysts, active metal covers the acid center, resulting in mismatch between the hydrogenation capacity and the ring opening capacity, and the process flow is long and energy consumption is high, making it difficult to prepare efficient ethylene cracking raw materials.

Method used

The active metal oxide is prepared first to avoid the active metal covering the acid center, and the catalyst preparation method is prepared by a "one-step method", combining small and large pores, USY molecular sieve and amorphous silicon and aluminum, to improve the matching of the catalyst's hydrogenation capacity and ring opening capacity.

Benefits of technology

It significantly improves the performance of the catalyst, achieves high tail oil yield and low tail oil BMCI value, simplifies the preparation process, reduces energy consumption, and can produce high-quality ethylene cracking raw materials for maximum volume.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a hydrocracking catalyst for increasing the yield of ethylene cracking raw materials and a preparation method thereof. The hydrocracking catalyst comprises the following components: a) group VIII metal or an oxide thereof, b) group VIB metal or an oxide thereof, c) small-pore-volume pseudo-boehmite, d) large-pore-volume pseudo-boehmite, e) a USY molecular sieve and f) amorphous silica-alumina. According to the catalyst prepared by the invention, an acid center is prevented from being covered by active metal, the acid amount of the catalyst is increased, and the catalyst has the advantages of high tail oil yield, low tail oil BMCI value and the like when being used for preparing an ethylene cracking raw material by hydrocracking, so that the catalyst has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a hydrocracking catalyst for producing more ethylene cracking raw materials and a preparation method thereof. Background Art

[0002] Reducing oil production and increasing chemical production is an effective way to solve the contradiction between the supply and demand of my country's oil surplus and shortage of chemical raw materials. The transformation of oil refining to chemical raw materials such as olefins and aromatics has become a definite trend. Due to the tight supply of raw materials for ethylene production in my country, it is necessary to broaden the source of raw materials and improve the quality of raw materials through technical means to ensure the stable development of my country's ethylene industry. As the leading product of petrochemicals, the output and cost of ethylene will be directly related to the overall economic benefits of my country's petrochemical industry. Under normal circumstances, the cost of steam cracking raw materials accounts for 60% to 80% of the total cost of ethylene. In recent years, hydrocracking tail oil has become the first choice for expanding the source of ethylene raw materials, optimizing the raw material structure, and improving the economic benefits of enterprises. Therefore, refineries have greatly increased the production of hydrocracking tail oil. Various hydrocracking processes such as high-pressure hydrocracking, mild hydrocracking and medium-pressure hydromodification can effectively change the group composition of vacuum wax oil. Compared with vacuum wax oil, the resulting hydrocracking tail oil has a similar distillation range, but the tail oil fraction of the hydrocracking product has the characteristics of high paraffin mass fraction and low BMCI value, which is a high-quality steam cracking ethylene raw material. The development of hydrocracking technology to increase the production of ethylene cracking raw materials is of great practical significance for further alleviating the tense situation of insufficient supply of ethylene raw materials in my country, improving the ethylene yield of cracking units, and extending the operation cycle of cracking furnaces.

[0003] As a hydrocracking technology for the efficient conversion of heavy oil to produce high-quality ethylene cracking raw materials, in order to achieve a major technological breakthrough, it is necessary to deeply consider improving the quality of hydrocracking tail oil by improving the performance of ethylene cracking raw material type hydrocracking catalysts, so as to lay a solid technical foundation for refining enterprises to better and faster achieve the transformation and development from oil refining type to chemical type. The hydrocracking catalyst currently used is a bifunctional catalyst, which is mainly composed of a metal component that provides hydrogenation / dehydrogenation function and an acidic component that provides cracking function. The metal component is usually selected from W-Ni, Mo-Ni, Mo-Co and W-Mo-Ni, Mo-Ni-Co and other metals, and the acidic component is usually selected from Y-type molecular sieve, β molecular sieve, amorphous silicon aluminum, etc. Patent CN 1175481A uses a traditional impregnation method to prepare a high-activity hydrocracking catalyst. The impregnation solution is composed of ammonium metatungstate and nickel nitrate. The carrier containing Y molecular sieve and refractory non-polar oxide is impregnated, and the performance of the prepared catalyst is significantly improved.

[0004] Patent CN 114433207A discloses a catalyst prepared by mixing, molding, drying and calcining Al-SBA-15 / Y core-shell composite molecular sieve, macroporous alumina and a binder, which has the characteristics of high tail oil yield and low tail oil BMCI value.

[0005] Patent CN 102049277A discloses a method of using a bicrystalline Y molecular sieve as a cracking component of a hydrocracking catalyst to prepare a hydrocracking catalyst capable of producing high-quality tail oil ethylene cracking feedstock.

[0006] Patent CN 102441411A discloses a method for preparing a high-activity, high-middle distillate oil selectivity hydrocracking catalyst using a co-precipitation method. The catalyst uses amorphous silicon-alumina as a carrier, a specially modified Y-type molecular sieve as an acidic component, a Group VIB metal and a Group VIII metal as hydrogenation active components, and a Group IVB metal as a co-catalyst, achieving good results.

[0007] In the relevant research on hydrocracking catalysts for producing ethylene cracking raw materials, Y-type molecular sieves, amorphous silica-alumina and alumina have been used respectively, and Y-type molecular sieves need to be modified. At the same time, the catalyst preparation generally adopts the traditional method of preparing the carrier first and then impregnating the active metal. During the impregnation process, the active metal will enter the molecular sieve pores and cover the acid center, which will reduce the catalyst's ring-opening ability, resulting in a mismatch between the catalyst's hydrogenation ability and the ring-opening ability. In addition, secondary calcination is required after impregnation, which has the disadvantages of long process and high energy consumption. Summary of the invention

[0008] In view of the deficiencies of the prior art, the present invention provides a hydrocracking catalyst capable of producing more ethylene cracking raw materials and a preparation method thereof.

[0009] To achieve the above object, the present invention adopts the following technical solutions: One of the purposes of the present invention is to protect a hydrocracking catalyst for producing high-yield ethylene cracking raw materials, which catalyst comprises the following components: a) a metal of Group VIII or its oxide; b) a metal of Group VIB or its oxide; c) small-pore pseudo-boehmite; d) large-pore pseudo-boehmite; e) USY molecular sieve; and f) amorphous silica-alumina.

[0010] In the above technical solution, the amount of component a) is 1-10 parts by weight, preferably 4-9 parts.

[0011] In the above technical solution, the amount of component b) is 1-35 parts by weight, preferably 15-30 parts.

[0012] In the above technical solution, the amount of component c) is 20-80 parts by weight, preferably 30-60 parts.

[0013] In the above technical solution, the amount of component d) is 1-30 parts by weight, preferably 5-25 parts.

[0014] In the above technical solution, the amount of component e) is 1-40 parts by weight, preferably 10-30 parts.

[0015] In the above technical solution, the amount of component f) is 1-50 parts by weight, preferably 20-40 parts.

[0016] Furthermore, the Group VIII metal or its oxide contains at least one of Co and Ni.

[0017] Furthermore, the VIB Group metal or its oxide contains at least one of Mo and W.

[0018] Furthermore, the specific surface area of ​​the small pore volume pseudo-boehmite is 150-400 m 2 / g, preferably 200~270m 2 / g; the total pore volume is 0.4~1.0 m³ / g, preferably 0.5~0.7 m³ / g; the average pore diameter is 5-12nm, preferably 6-9nm; the peptization index is above 98%.

[0019] Furthermore, the specific surface area of ​​the macroporous pseudo-boehmite is 150-400 m 2 / g, preferably 180~250m 2 / g; the total pore volume is 0.7~1.5m³ / g, preferably 0.9~1.2 m³ / g; the average pore diameter is 8-25nm, preferably 12-18nm; the peptization index is 5~30%, preferably 10~20%.

[0020] Furthermore, the specific surface area of ​​the USY molecular sieve is 500-1000 m 2 / g, preferably 600~800 m 2 / g; total pore volume is 0.4~1.0 m³ / g, preferably 0.5~0.7 m³ / g; the molar ratio of silicon oxide / aluminum oxide is 10~30, preferably 10-20; the unit cell parameter is 2.43~2.45nm; the relative crystallinity is above 90%.

[0021] Furthermore, the specific surface area of ​​the amorphous silicon aluminum is 200-600 m 2 / g, preferably 300-500㎡ / g; the total pore volume is 0.4~1.5 m³ / g, preferably 0.6~0.9 m³ / g; the silicon oxide content is 20-70wt%, preferably 40-60wt%.

[0022] The second object of the present invention is to provide a method for preparing the hydrocracking catalyst, which comprises the following steps: (1) dissolving a compound containing a VIB group element and a compound containing a VIII group element in a solvent to obtain a mixed metal solution; (2) slowly adding amorphous silicon aluminum to the mixed metal solution obtained in step (1), stirring evenly, drying, crushing, and sieving to obtain metal-containing amorphous silicon aluminum; (3) The large-pore pseudo-boehmite, small-pore pseudo-boehmite, USY molecular sieve and the metal-containing amorphous silica-alumina obtained in step (2) are uniformly mixed, and then an acid solution is added. After being fully kneaded, the mixture is molded, and then dried and calcined to obtain the hydrocracking catalyst.

[0023] Furthermore, the solvent in step (1) is water, an inorganic acid such as nitric acid, hydrochloric acid, phosphoric acid, or an organic acid such as formic acid, acetic acid.

[0024] Furthermore, the drying temperature in step (2) is 100-200° C., preferably 120-140° C.; the drying time is 2-10 hours, preferably 4-8 hours.

[0025] Furthermore, the sieving in step (2) uses a sieve with a mesh size of 300 or more.

[0026] Furthermore, the acid solution in step (3) is an aqueous solution of an inorganic acid such as nitric acid, nitric acid, sulfuric acid, or an organic acid such as formic acid, acetic acid, citric acid, and the like, and its concentration is 0.5-3 wt %, preferably 2-1.5 wt %.

[0027] Furthermore, the calcination temperature in step (3) is 400-600° C., preferably 450-550° C., and the calcination time is 2-10 hours, preferably 4-6 hours.

[0028] The present invention prepares active metal oxides first, thereby avoiding active metal covering the acid center and increasing the acid content of the catalyst. Then, a "one-step" catalyst preparation method is used and a certain proportion of macroporous pseudo-boehmite is added to effectively improve the matching of the catalyst's hydrogenation capacity and ring-opening capacity, reduce secondary reactions such as chain breaking of alkanes, and prepare a catalyst with high tail oil yield and low tail oil BMCI value.

[0029] The significant advantages of the present invention are: (1) Compared with the existing catalyst preparation technology, the catalyst prepared by the method of the present invention has excellent performance, can reduce the BMCI of the tail oil while ensuring a high yield of the tail oil, thereby achieving the maximum production of high-quality ethylene cracking feedstock.

[0030] (2) The preparation method of the catalyst of the present invention is simple, the process flow is short, and no secondary calcination is required, thereby reducing the energy consumption in the catalyst production process.

[0031] (3) Compared with the traditional catalyst preparation method, the catalyst prepared by the present invention avoids the active metal covering the acid center and increases the acid content of the catalyst. DETAILED DESCRIPTION

[0032] A hydrocracking catalyst for producing high-yield ethylene cracking raw materials, comprising the following components and usage: a) 1-10 parts of Group VIII metal or its oxide, b) 1-35 parts of Group VIB metal or its oxide, c) 20-80 parts of small-pore pseudo-boehmite, d) 1-30 parts of large-pore pseudo-boehmite, e) 1-40 parts of USY molecular sieve, and f) 1-50 parts of amorphous silicon aluminum.

[0033] Wherein, the Group VIII metal or its oxide contains at least one of Co and Ni.

[0034] The VIB Group metal or its oxide contains at least one of Mo and W.

[0035] The specific surface area of ​​the small-pore pseudo-boehmite is 150-400 m 2 / g, the total pore volume is 0.4~1.0 m³ / g, the average pore diameter is 5-12nm, and the peptization index is above 98%.

[0036] The specific surface area of ​​the macroporous pseudo-boehmite is 150-400 m 2 / g, the total pore volume is 0.7~1.5m³ / g, the average pore diameter is 8-25nm, and the peptization index is 5~30%.

[0037] The specific surface area of ​​the USY molecular sieve is 500-1000 m 2 / g, the total pore volume is 0.4~1.0 m³ / g, the molar ratio of silicon oxide / aluminum oxide is 10~30, the unit cell parameter is 2.43~2.45nm, and the relative crystallinity is more than 90%.

[0038] The specific surface area of ​​the amorphous silicon aluminum is 200-600 m 2 / g, the total pore volume is 0.4~1.5 m³ / g, and the silicon oxide content is 20-70wt%.

[0039] The preparation method of the hydrocracking catalyst comprises the following steps: (1) dissolving a compound containing a VIB group element and a compound containing a VIII group element in a solvent to obtain a mixed metal solution; (2) slowly adding amorphous silicon aluminum to the mixed metal solution obtained in step (1), stirring evenly, drying at 100-200° C. for 2-10 hours, crushing, and passing through a 300-mesh sieve to obtain metal-containing amorphous silicon aluminum; (3) The large-pore pseudo-boehmite, the small-pore pseudo-boehmite, the USY molecular sieve and the metal-containing amorphous silica-alumina obtained in step (2) are uniformly mixed, and then an acid solution with a concentration of 0.5-3 wt% is added, and the mixture is fully kneaded and formed, and then dried and calcined at 400-600° C. for 2-10 hours to obtain the obtained product.

[0040] Wherein, the solvent in step (1) is water, an inorganic acid such as nitric acid, hydrochloric acid, phosphoric acid, or an organic acid such as formic acid, acetic acid.

[0041] The acid solution in step (3) is an aqueous solution of an inorganic acid such as nitric acid, nitric acid, sulfuric acid, or an organic acid such as formic acid, acetic acid, citric acid, etc.

[0042] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0043] Example 1 (1) By weight, 6 parts of nickel oxide and 22 parts of tungsten oxide were dissolved in a 1 wt% nitric acid solution, and 20 parts of amorphous silicon aluminum (dry basis content: 74 wt%, calculated as oxides: aluminum oxide content: 60 wt%, silicon oxide content: 40 wt%) were slowly added, stirred evenly, dried at 120°C for 6 hours, crushed, and passed through a 300 mesh sieve to collect the resulting powder.

[0044] (2) 10 parts of large pore volume pseudo-boehmite (dry content of 70wt%, pore volume of 1.1 m³ / g), 30 parts of small pore volume pseudo-boehmite (dry content of 71wt%, pore volume of 0.5 m³ / g), 12 parts of USY molecular sieve powder (dry content of 79wt%) and the powder obtained in step (1) were mixed evenly, and then 2wt% nitric acid solution was added, and after being fully kneaded, it was extruded into clover strips with a length of 3-10 mm and a diameter of 1.8 mm. Dry at room temperature for 4 hours (turn it twice in the middle), then dry at 120°C for 4 hours, and calcine at 500°C for 6 hours to obtain catalyst CAT-1.

[0045] Example 2 (1) 6 parts of nickel oxide and 22 parts of tungsten oxide were weighed and dissolved in 1 wt% nitric acid solution, and 20 parts of amorphous silicon aluminum (dry basis content: 74 wt%, calculated as oxides: aluminum oxide content: 60 wt%, silicon oxide content: 40 wt%) were slowly added, stirred evenly, dried at 120°C for 6 hours, crushed, and sieved through a 300-mesh sieve to collect the resulting powder.

[0046] (2) 20 parts of large pore volume pseudo-boehmite (dry content of 70wt%, pore volume of 1.1 m³ / g), 20 parts of small pore volume pseudo-boehmite (dry content of 71wt%, pore volume of 0.5 m³ / g), 12 parts by weight of USY molecular sieve powder (dry content of 79wt%) and the powder obtained in step (1) were mixed evenly, and then 2wt% nitric acid solution was added, and after being fully kneaded, it was extruded into clover strips with a length of 3-10 mm and a diameter of 1.8 mm. Dry at room temperature for 4 hours (turn it twice in the middle), then dry at 120°C for 4 hours, and calcine at 500°C for 6 hours to obtain catalyst CAT-2.

[0047] Example 3 (1) 3 parts of nickel oxide and 14 parts of tungsten oxide were weighed and dissolved in 1 wt% nitric acid solution, and 20 parts of amorphous silicon aluminum (dry basis content: 74 wt%, calculated as oxides: aluminum oxide content: 60 wt%, silicon oxide content: 40 wt%) were slowly added, stirred evenly, dried at 120°C for 6 hours, crushed, and passed through a 300 mesh sieve to collect the resulting powder.

[0048] (2) 12 parts of large pore volume pseudo-boehmite (dry content of 70wt%, pore volume of 1.1 m³ / g), 35 parts of small pore volume pseudo-boehmite (dry content of 71wt%, pore volume of 0.5 m³ / g), 16 parts of USY molecular sieve powder (dry content of 79wt%) and the powder obtained in step (1) were mixed evenly, and then 2wt% nitric acid solution was added, and after fully kneading, it was extruded into clover strips with a length of 3-10 mm and a diameter of 1.8 mm. Dry at room temperature for 4 hours (turn twice in the middle), then dry at 120°C for 4 hours, and calcine at 500°C for 6 hours to obtain catalyst CAT-3.

[0049] Comparative Example 1 (1) By weight, 10 parts of large pore volume pseudo-boehmite (dry basis content of 71wt%, pore volume of 1.1 m³ / g), 30 parts of small pore volume pseudo-boehmite (dry basis content of 71wt%, pore volume of 0.5 m³ / g), 12 parts of USY molecular sieve powder (dry basis content of 79wt%), 20 parts of amorphous silica-alumina (dry basis content of 74wt%, calculated as oxide, aluminum oxide content of 60wt%, silicon oxide content of 40wt%) were mixed evenly, and then 2wt% nitric acid solution was added, and after fully kneading, it was extruded into clover strips with a length of 3-10 mm and a diameter of 1.8 mm. Dry at room temperature for 4 hours (turn twice in the middle), then dry at 120℃ for 4 hours, and calcine at 500℃ for 6 hours to obtain a catalyst carrier; (2) 6 parts of nickel oxide and 22 parts of tungsten oxide were dissolved in 1 wt% nitric acid solution, and the catalyst carrier obtained in step (1) was impregnated with equal volumes, and then rotary dried at 130°C for 5 hours and calcined at 500°C for 5 hours to obtain catalyst CAT-4.

[0050] Comparative Example 2 (1) By weight, 6 parts of nickel oxide and 22 parts of tungsten oxide were dissolved in a 1 wt% nitric acid solution, and 20 parts of amorphous silicon aluminum (dry basis content: 74 wt%, calculated as oxides: aluminum oxide content: 60 wt%, silicon oxide content: 40 wt%) were slowly added, stirred evenly, dried at 120°C for 6 hours, crushed, and passed through a 300 mesh sieve to collect the resulting powder.

[0051] (2) 40 parts of small pore volume pseudo-boehmite (dry basis content of 71wt%, pore volume of 0.5m³ / g), 12 parts of USY molecular sieve powder (dry basis content of 79wt%) and the powder obtained in step (1) were mixed evenly, and then 2wt% nitric acid solution was added, and after being fully kneaded, they were extruded into clover strips with a length of 3-10 mm and a diameter of 1.8 mm. Dry at room temperature for 4 hours (turn twice in the middle), then dry at 120°C for 4 hours, and calcine at 500°C for 6 hours to obtain catalyst CAT-5.

[0052] Comparative Example 3 (1) By weight, 6 parts of nickel oxide and 22 parts of tungsten oxide were dissolved in a 1 wt% nitric acid solution, and 20 parts of amorphous silicon aluminum (dry basis content: 74 wt%, calculated as oxides: aluminum oxide content: 60 wt%, silicon oxide content: 40 wt%) were slowly added, stirred evenly, dried at 120°C for 6 hours, crushed, and passed through a 300 mesh sieve to collect the resulting powder.

[0053] (2) 40 parts of macroporous pseudo-boehmite (dry basis content of 71wt%, pore volume of 1.1 m³ / g), 12 parts of USY molecular sieve powder (dry basis content of 79wt%) and the powder obtained in step (1) were mixed evenly, and then 2wt% nitric acid solution was added, and after being fully kneaded, they were extruded into clover strips with a length of 3-10 mm and a diameter of 1.8 mm. Dry at room temperature for 4 hours (turn twice in the middle), then dry at 120°C for 4 hours, and calcine at 500°C for 6 hours to obtain catalyst CAT-6.

[0054] Comparative Example 4 (1) By weight, 6 parts of nickel oxide and 22 parts of tungsten oxide were dissolved in a 1 wt% nitric acid solution, and 20 parts of amorphous silicon aluminum (dry basis content: 74 wt%, calculated as oxides: aluminum oxide content: 60 wt%, silicon oxide content: 40 wt%) were slowly added, stirred evenly, dried at 120°C for 6 hours, crushed, and passed through a 300 mesh sieve to collect the resulting powder.

[0055] (2) 10 parts of large-pore pseudo-boehmite (dry basis content of 71wt%, pore volume of 1.1 m³ / g) and 42 parts of small-pore pseudo-boehmite (dry basis content of 71wt%, pore volume of 0.5 m³ / g) were mixed evenly with the powder obtained in step (1), and then 2wt% nitric acid solution was added. After fully kneading, the mixture was extruded into clover strips with a length of 3-10 mm and a diameter of 1.8 mm. The mixture was dried at room temperature for 4 hours (turned twice in the middle), then dried at 120°C for 4 hours, and calcined at 500°C for 6 hours to obtain catalyst CAT-7.

[0056] Catalyst performance test The performance of the catalysts prepared in the embodiments and comparative examples was tested. The test was conducted using a two-stage 100 ml small-scale hydrogenation evaluation device in series. The first reactor was filled with UOP's hydrorefining catalyst KF848, and the second reactor was filled with the hydrocracking catalyst prepared in the embodiments or comparative examples, and the two reactors were used in series. After the catalyst was online sulfurized, the feedstock oil (the properties of the feedstock oil are shown in Table 1) and hydrogen passed through the two reactors in sequence (reactor condition parameter settings are shown in Table 2), and the effluent from the second reactor was the hydrocracking oil. After cutting with a petroleum product distillation tester, the oil products of each component were obtained for evaluating the catalyst performance. The results are shown in Table 3.

[0057] Table 1 Raw oil properties

[0058] Table 2 Reactor condition parameters

[0059] Table 3 Catalyst performance evaluation results

[0060] As can be seen from the results in Table 3, the use of the catalyst prepared in the embodiment to react can obtain a higher tail oil yield and a lower tail oil BMCI value. In contrast, the catalyst prepared by the traditional equal volume impregnation method (Comparative Example 1) has a low total acid content, indicating that its active center is covered, which leads to a high BMCI value of the tail oil and a low paraffin content; the catalyst using only macroporous pseudo-boehmite or small-pore pseudo-boehmite (Comparative Examples 2 and 3) has a high BMCI value of the tail oil and a low paraffin content, although the total acid content is increased; the catalyst prepared without using molecular sieves (Comparative Example 4) has an extremely low total acid content and a very high BMCI value of the tail oil.

[0061] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A hydrocracking catalyst for producing more ethylene cracking feedstock, characterized in that: The components and amounts of the catalyst are as follows: a) 1-10 parts of a Group VIII metal or its oxide; b) 1-35 parts of a metal of Group VIB or its oxide; c) 20-80 parts of small pore volume pseudo-boehmite; d) 1-30 parts of macroporous pseudo-boehmite; e) 1-40 parts of USY molecular sieve; f) 1-50 parts of amorphous silicon aluminum.

2. The catalyst having a hydrocracking effect according to claim 1, characterized in that: The Group VIII metal or its oxide contains at least one of Co and Ni.

3. The catalyst having a hydrocracking effect according to claim 1, characterized in that: The VIB Group metal or its oxide contains at least one of Mo and W.

4. The catalyst having a hydrocracking effect according to claim 1, characterized in that: The specific surface area of ​​the small-pore pseudo-boehmite is 150-400 m 2 / g, the total pore volume is 0.4~1.0 m³ / g, the average pore diameter is 5-12 nm, and the peptization index is above 98%.

5. The catalyst having a hydrocracking effect according to claim 1, characterized in that: The specific surface area of ​​the macroporous pseudo-boehmite is 150-400 m 2 / g, the total pore volume is 0.7~1.5 m³ / g, the average pore diameter is 8-25 nm, and the peptization index is 5~30%.

6. The catalyst having a hydrocracking effect according to claim 1, characterized in that: The specific surface area of ​​the USY molecular sieve is 500-1000 m 2 / g, the total pore volume is 0.4~1.0 m³ / g, the molar ratio of silicon oxide to aluminum oxide is 10~30, the unit cell parameter is 2.43~2.45nm, and the relative crystallinity is more than 90%.

7. The catalyst having a hydrocracking effect according to claim 1, characterized in that: The specific surface area of ​​the amorphous silicon aluminum is 200-600 m 2 / g, the total pore volume is 0.4~1.5m³ / g, and the silicon oxide content is 20-70wt%.

8. A method for preparing a hydrocracking catalyst as claimed in claim 1, characterized in that: The steps include: (1) dissolving a compound containing a VIB group element and a compound containing a VIII group element to obtain a mixed metal solution; (2) slowly adding amorphous silicon aluminum to the mixed metal solution obtained in step (1), stirring evenly, drying, crushing, and sieving to obtain metal-containing amorphous silicon aluminum; (3) The large-pore pseudo-boehmite, small-pore pseudo-boehmite, USY molecular sieve and the metal-containing amorphous silica-alumina obtained in step (2) are uniformly mixed, and then an acid solution is added. After being fully kneaded, the mixture is molded, and then dried and calcined to obtain the hydrocracking catalyst.

9. The method for preparing a hydrocracking catalyst according to claim 8, characterized in that: The acid solution in step (3) is an aqueous solution of an inorganic acid or an organic acid, and its concentration is 0.5-3 wt %.

10. The method for preparing a hydrocracking catalyst according to claim 8, characterized in that: The calcination temperature in step (3) is 400-600° C. and the calcination time is 2-10 hours.

Citation Information

Patent Citations

  • Hydrocracking catalyst for producing naphtha and raw material for preparing ethylene

    CN102049277A

  • Hydrocracking catalyst with high activity and high-medium oil selectivity and preparation method of hydrocracking catalyst

    CN102441411A

  • Co-impregnation liquid for preparing hydrocracking catalyst

    CN1175481A